Marine ecosystems and global change - Barange, Manuel 1961-. (Oxford Oxford University Press, 2010)
Global changes, including climate change and intensive fishing, are having significant impacts on the world's oceans. This book advances knowledge of the structure and functioning of marine ecosystems and their major sub-systems, and how they respond to physical forcing.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Marine ecology; Climatic changes; Marine ecosystem management